THE IMPACT OF FINANCIAL MALPRACTICES ON THE PRODUCTIVITY OF THE PUBLIC SECTOR IN NIGERIA: A CASE STUDY OF FEDERAL INLAND REVENUE, ENUGU STATE - Iloh, Angela Ugo; Adie, Alexandera Nkechi (African Journal of Social and Behavioural Sciences, 2023)
This study examined the Impact of Financial Malpractice on the Productivity of Nigeria Public Sector (A case Study of Federal Inland Revenue (FIRS), Enugu State). Financial Malpractice may occur when a financial professional fails to make suitable financial report or records of actual transactions or trades as ordered by the financial regulations/rules guiding the operations of Public Financial Management. For instance, charging excessive fees or commits theft or fraud/embezzlement of funds, misappropriation of funds, etc., these may also be considered as financial malpractice in the public services. The investigation was prompted because the researcher observed the poor state of Nigeria economy and the poor service delivery by public officials. The objective of the study was to examine if financial malpractice exists in the public sector and to know its effects on the nation’s economy and the productivity of workers. It is hoped that the study will help to enlighten the government and the citizens on the danger of financial malpractice. The study was a descriptive in nature. The population of the study area was 140. The source of data was mainly secondary data with the aid of textbooks, journals, official publications, etc., and also observations made by the researcher. The method of data analysis was quantitative in nature. The researcher was guided by the crime opportunity theory as a theoretical framework of analysis. Findings from the study revealed that; financial malpractices exist in the public service and becoming a norm, most stakeholders are perpetrators of it; that the control system is weak, it affects both the national economy and the output of workers. The government has strategies to control malpractices but it is inadequate. The study therefore, recommends that government should establish more strategies of control, monitoring and evaluations of accounting procedures and also ensure offenders are brought to book by the law. Finally, advanced technological equipment, like CCTIVs should be installed in public offices to monitor activities.